The Implications of the Arabic Artificial Environment at MBS Al Islam Paleran Jember as the Basis for Akhlak Education - Hasna' Huwaida; Supiah; Dhofir Catur Bashori (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2026)
Technology development has an effect on society’s declining akhlak standards. Teachers are being forced to put in more effort to sustain and preserve akhlak values in their students as a result of this moral decline. Pesantren institutions that have a hidden curriculum, one that is developed throughout the day for a whole week, are one example of efforts in this direction. Learning Arabic is one of the lessons that contributes to this akhlak education; it aims to impart Islamic principles in addition to language skills. The creation of an artificial environment (bi’ah lughawiyyah) as a direct and authentic Arabic language experience is one of the Arabic language learning methodologies that this study highlights.This study was conducted in the field at Muhammadiyah Boarding School Al Islam Paleran Jember, one of Muhammadiyah’s boarding schools. In order to accomplish this, the author employed a qualitative methodology, gathering data through observation, interviews, and documentation. Additionally, the Miles and Huberman model was used for data analysis. The objective is to outline artificial environment-based Arabic language learning activities offered by MBS Al Islam Paleran, explain how akhlak education is implemented there, and discuss the implications of this bi’ah lughawiyyah for students.The study’s findings clarify the significance of learning Arabic with a clear conceptualization within the framework of akhlak education, particularly with regard to speech, manners, self-confidence, responsibility, and discipline. This language environment requires complete support in terms of infrastructure, supporting facilities, as well as teacher quality.